Ergonomic rationalization of transmitted vibration to hands of the workers. (March 2017) - Flimel, Marián; Dupláková, Darina
This article focuses on the solution of optimal workers' load in transmitted vibration to hands. Ergonomic rationalization comes from the application of organizational methods and the possibilities of an innovative technical solution. Attention is paid to the method of job rotation declared in the system solution within organizational methods. The sequence of the application is introduced by algorithm within strategic company planning and by a sequence chain within the operative solution. Determination of the optimal exposition period through transmitted vibration from the tools and machines to the hands of the workers is possible according to a set representative table or graphic instruments. A realized example of manually controlled machine modification – a vibration board used in the building industry is described within an experiment. The admissible exposition value before and after modification is calculated by measuring the acceleration of the vibration of "a". The possibility of five times longer expansion of the working time period during the work shift comes after vibro-isolation modifications of the mentioned machine. The meaning of rationalization steps consists of the participation of employees on its solution within the operation conditions.